Ŝodo problemi ob′êktìv socìal′no - zabezpečuval′nih pravovìdnosin - Sinčuk, Svìtlana (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The author substantiates theoretically the notion, legal features and types of social security provision as an integrated object of the similar legal relations; the author argues the necessity of the Ukraine’s legislation improvement by its adaptation to the theory of the legal relations’ object.
Keywords: ustawodawstwo Ukrainy; zabezpieczenie społeczne; stosunki prawne